Complete Genome Sequences of Two Dengue Virus Serotype 1 Genotype V Strains from Different Lineages - Vedovello, Danila; Menegaldo, Tauyne; Biselli-Perico, Joice M.; Ullmann, Leila Sabrina [UNESP]; Araujo Junior, Joao Pessoa [UNESP]; Nogueira, Mauricio Lacerda (Amer Soc Microbiology, 2016)
Previous phylogenetic studies involving dengue virus serotype 1 (DENV 1) have shown several lineages of genotype V circulating worldwide. After sequencing the complete genome of strains from Sao Jose do Rio Preto, Sao Paulo, Brazil, we identified a list of 50 different amino acids that differ between the two lineages, announced here.